Industrial Chic: Fashion Shows in Readymade Spaces. (2nd January 2019) - Strömberg, Per
Abstract: The staging concept of adaptive reuse is a strategy that is being repeated at many fashion weeks, creating a subgenre of alternative runway spaces. Why does the fashion industry locate its runway shows in obsolete factories, derelict subway stations, and worn-out warehouses? The spectacular show of H&M in 2001, staged in an old limestone quarry in Sweden, is used as a point of reference for this discussion which is centered on the question: how are cultural reuse values being negotiated, reproduced, and commodified? The author considers the postindustrial fashion show space to be a "readymade space" in the terminology of art theory. These runway spaces are a part of an overall "cultural economy of reuse" for which cultural intermediators play a significant role. The main conclusion of this paper is that adaptive reuse has several functions, of which the aesthetic is most important because of its potential for evoking "authenticity" and subcultural "creativity." Here, adaptive reuse is a sort of re-appropriation of the subversive tactics of the artistic avant-garde, of new social movements, and of alternative urban lifestyles. Their subversive expression is spatially converted into a stylistic contrast or a lifestyle statement, which can then be converted into economic capital.